Impact of Pembrolizumab Versus Chemotherapy as Second-Line Therapy for Advanced Esophageal Cancer on Health-Related Quality of Life in KEYNOTE-181. Issue 4 (1st February 2022) - Adenis, Antoine; Kulkarni, Amit S.; Girotto, Gustavo C.; de la Fouchardiere, Christelle; Senellart, Helene; van Laarhoven, Hanneke W. M.; Mansoor, Wasat; Al-Rajabi, Raed; Norquist, Josephine; Amonkar, Mayur; Suryawanshi, Shailaja; Bhagia, Pooja; et al.
Abstract : PURPOSE: In the phase III KEYNOTE-181 study (NCT02564263 ) of patients with advanced esophageal cancer (EC), pembrolizumab monotherapy prolonged overall survival versus chemotherapy as second-line therapy in patients with programmed death ligand 1 combined positive score (CPS) ≥ 10. We present the results of the prespecified health-related quality-of-life (HRQoL) analyses of the squamous cell carcinoma (SCC), CPS ≥ 10, and CPS ≥ 10 SCC populations. PATIENTS AND METHODS: HRQoL was measured using the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30), EORTC QLQ EC questionnaire (OES18), and EuroQol 5-dimension questionnaire (EQ-5D). Data were analyzed in patients who received ≥ 1 dose of study treatment and completed ≥ 1 HRQoL assessment. Key analyses included baseline to week 9 least squares mean change in global health status/quality of life, functional or symptom subscales, and time to deterioration (≥ 10-point deterioration) for specific subscales. RESULTS: The HRQoL population included 387 patients with SCC. Compliance and completion rates for all three questionnaires were similar in both treatment groups at baseline and week 9. No clinically meaningful differences in global health status/quality of life scores were observed between treatment groups from baseline to week 9 (least squares mean difference, 2.80; 95% CI, –1.48 to 7.08); patients in both treatment groups generally exhibited stable functioning and symptom scores of the QLQ-C30 and QLQ-OES18 from baseline to week 9. Time to deterioration for pain (hazard ratio [HR], 1.22; 95% CI, 0.79 to 1.89), reflux (HR, 2.38; 95% CI, 1.33 to 4.25), and dysphagia (HR, 1.53; 95% CI, 1.02 to 2.31) subscales were similar between treatment groups. These findings were generally similar in the CPS ≥ 10 (n = 218) and CPS ≥ 10 SCC (n = 166) subgroups. CONCLUSION: In patients with advanced EC, pembrolizumab monotherapy and chemotherapy maintained HRQoL in patients with SCC, CPS ≥ 10, and CPS ≥ 10 SCC.